Fulminant fatal pneumonia and bacteremia due to Aeromonas dhakensis in an immunocompetent man: a case report and literature review - Jiang, Lei; Zhao, Qiquan; Li, Dairong; Gao, Jia; Zhang, Xiaobing; Shu, Qian; Han, Xiaoli (Frontiers in Cellular and Infection Microbiology, 2024)
Background Aeromonas dhakensis is associated with soft tissue infection, bacteremia and gastroenteritis. Involvement of respiratory system in adults is extremely rare. We report a case of fulminant pneumonia and bacteremia due to A. dhakensis in a patient without underlying diseases. Case presentation A 26-year-old man became ill suddenly with pneumonia after swimming in a river. Despite intensive support measures in the intensive care unit, he died 13 hours after admission and 4 days after his first symptoms. Autopsy showed abundant Gram-negative bacteria, massive inflammatory cell infiltration, edema, necrosis and hemorrhage in lung tissue. A. dhakensis was isolated from blood culture taken at admission and bronchoalveolar lavage fluid (BALF) after intubation. Moreover, A. dhakensis was also detected in lung tissue by metagenomic next-generation sequencing (mNGS) assay. The infection may have come from river water. Conclusion In patients who develop a fulminant pneumonia after contacting an aquatic environment, A. dhakensis should be alerted and mNGS may aid in the detection of aquatic pathogens by being more sensitive and specific versus traditional bacterial culture.